Analisis keuntungan usaha kepiting bakau (Scylla serrata) dengan alat tangkap bubu Desa Dampala Jaya Kecamatan Kulisusu Barat Kabupaten Buton Utara - Kurniawan, Andril; La Ola, La Onu; Rosmawati; Risfandi (Universitas Halu Oleo, 2025)
Entitled of this study is profits analysis of the manufacturing mud crab (Scylla serrata) business by using fish trap in the mangrove ecosystem of Dampala Jaya Village, West Kulisusu District, North Buton District. The aim of this study was to determine the profits of mangrove crab entrepreneurs in Dampala Jaya Village, West Kulisusu District, North Buton Regency. This research was conducted in November 2023. The sampling technique in this research used the purposive sampling method. Research data was obtained through surveys, observations, interviews and documentation. Data collected were consists of primary data and secondary data, and all data were analysed by using the cost analysis, revenue analysis and profit analysis. The total cost of this business was IDR 15,816,862/month with an average of IDR 1,581,686/month. The amount of revenue from this business was IDR 48,000,000/month with an average of IDR 4,800,000/month. Thus the profit obtained was IDR. 32,183,138/month with an average profit of IDR 3,218,313/month. Based on the data obtained, this business was profitable for the people who run it.